Exploring Ethnomathematics in the Traditional House of Suku Tengger: Bridging Structures and Classrooms - Anwar, Lathiful; Sa’dijah, Cholis; Fauzan, Ahmad; Johar, Rahmah; ., Sugiman; Cahyani, Septi Dwi (Journal of Ecohumanism, 2024)
This ethnomathematics study explores the interplay of mathematical principles and cultural practices in the Suku Tengger society, focusing on traditional housing construction. The data of this study were based on the interview session with the traditional leader who comprehend the structural aspect of the traditional house and cultural tradition involved in constructing the house, and the blue-print of the structural architecture of the house. Thematic analysis was conducted to analyze the data aiming to identify the integration of the mathematical principles and potential contexts and activities that can be integrated in the mathematical classroom. Our findings show that there are several mathematical principles integrated in the structural element of the house namely the concept of tangent, arithmetic modulo (mod(5)), and measurement and geometry. Our results suggest learning sequences that are notably well-organized and integrate reflective approaches, digital simulations, and practical activities. Specifically, this study posits that emerging technologies like augmented reality could further democratize and enrich the educational experience, providing a window into the cultural dimensions of mathematics for a diverse student body. Additional research is required to fully understand the effects of cultural context on geometric abilities, including spatial abilities, and how to improve accessibility and inclusivity by utilizing augmented reality technology and other types of software geometry.